Checking Agriculture’s Pulse: Field Pea (Pisum Sativum L.), Sustainability, and Phosphorus Use Efficiency - Powers, Sarah E.; Thavarajah, Dil (Frontiers in Plant Science, 2019)
Investigations regarding the incorporation of better sustainable production strategies into current agricultural-food systems are necessary to grow crops that reduce negative impacts on the environment yet will meet the production and nutritional demand of 10 billion people by 2050. The introduction of organic, alternative staple food crops, such as nutrient-dense field pea (Pisum sativum L.), to the everyday diet, may alleviate micronutrient malnutrition and incorporate more sustainable agriculture practices globally. Varieties are grown in organic systems currently yield less than conventionally produced foods, with less bioavailable nutrients, due to poor soil nutrient content. One of the most limiting nutrients for field pea is phosphorus (P) because this legume crop requires significant inputs for nodule formation. Therefore, P use efficiency (PUE) should be a breeding target for sustainable agriculture and biofortification efforts; the important role of the soil microbiome in nutrient acquisition should also be examined. The objectives of this review are to highlight the benefits of field pea for organic agriculture and human health, and discuss nutritional breeding strategies to increase field pea production in organic systems. Field pea and other pulse crops are underrepresented in agricultural research, yet are important crops for a sustainable future and better food systems. Furthermore, because field pea is consumed globally by both developed and at-risk populations, research efforts could help increase global health overall and combat micronutrient malnutrition.